Anarchic occupation: Before and after study of the habitability of the Makasi cell in the town of Butembo in North Kivu/DR Congo - Isaac UZIMATI DJURUA (Jurnal Multidisiplin Indonesia, 2026)
The urban fabric of the Makasi Cell, in the city of Butembo (North Kivu/DRC), is in a very advanced state of degradation. This comparative study before and after habitability sheds light on the direct impacts of housing occupation. To do this, GPS (Global Positioning System) coordinates and those related to the physical condition of buildings and roads were used. The GIS and remote sensing methods were chosen to highlight the slope class dedicated to the constructible zone and that related to the degradation of the fabric. The ground truth required field inspection before, during, and after rain scenes. It emerged that 40.07% of the surface area was in the 0–2% slope range. This low slope of the non-building zone exposes the Makasi Cell to the risk of flooding where it is considered a thalweg. After a rainy scene, the waters of the neighboring cells take the route into the Makasi Cell, the majority of which stagnates due to the configuration. On the other hand, after habitability, it results in 51.22% of buildings being in poor condition or in critical condition, almost collapsed by the floods. There are 1,458 linear meters of traffic lanes which are in a very advanced state of disrepair.